The Study of the Concept of Exile: Re-reading Edward Said (Leadership, Education, Personality: An Interdisciplinary Journal, ISSN: 2524-6178, 2025)
The history of exile dates back old. There are instances of Ovid[1] and others being given the punishment of exile. The punishment may be due to social, political, economical, cultural or religious reasons. Etymologically theword ‘exile’ comes from the Latin word ‘exilum’ meaning banishment. Numerous thinkers have been subjected to undergo the hardship of banishment[2]. Exile as such has been the thematic concern for a countless number of literatures till today. It is one of the major characteristics of contemporary period yet as a concept and a condition it is hard to define owing to its complex and varied nature which subsequently invites multiple referents. Only few have come forth with clear and sound theories of exile. In this paper I will analyze the concept of exile from the perspectives of the twentieth- century thinker Edward Said. Furthermore, I will discuss how his perception of exile has molded the formation of varied other ideas in his works [1] Ovid is a Roman poet of 8th century A.D. His works include Amores, ArsAmotoria(Art of Love) and the epic poem Metamorphoses among others. He is banished to Tomis for reasons still unclear though he has stated in his Tristia that it is carmen et errori.e. “a poem and a mistake.” [2] Martin Tueker in his Literary Exile in the Twentieth Century (1991) has listed some 550 prominent exiles worldwide while Wikipedia has given the names of 144 notable people who have suffered the hardship of exile. Please see <http://en.wikipedia.org/wiki/Exile>